1999
DOI: 10.1128/jvi.73.1.120-127.1999
|View full text |Cite
|
Sign up to set email alerts
|

Nucleoporins Nup98 and Nup214 Participate in Nuclear Export of Human Immunodeficiency Virus Type 1 Rev

Abstract: Human immunodeficiency virus type 1 (HIV-1) Rev contains a leucine-rich nuclear export signal that is essential for its nucleocytoplasmic export mediated by hCRM1. We examined the role of selected nucleoporins, which are located in peripheral structures of the nuclear pore complex and are thought to be involved in export, in Rev function in human cells. First, we found that upon actinomycin D treatment, Nup98, but not Nup214 or Nup153, is able to translocate to the cytoplasm of HeLa cells, demonstrating that N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(69 citation statements)
references
References 51 publications
4
64
0
1
Order By: Relevance
“…3, row 1). As previously observed [28,30,31], Myc-Rev expression induced CRM1 relocalization and prominent colocalization of Rev and CRM1 in nucleoli ( Fig. 3, row 2).…”
Section: Crm1 Is Critical For the Nullbasic-mediated Redistribution Osupporting
confidence: 87%
“…3, row 1). As previously observed [28,30,31], Myc-Rev expression induced CRM1 relocalization and prominent colocalization of Rev and CRM1 in nucleoli ( Fig. 3, row 2).…”
Section: Crm1 Is Critical For the Nullbasic-mediated Redistribution Osupporting
confidence: 87%
“…The nucleolus is also emerging as an important target of various viral proteins [4]. Viral proteins targeting the nucleolus are for example implicated in the regulation of apoptosis, as shown with West Nile virus capsid protein, and in the regulation of viral mRNA export, as shown with human immunodeficiency virus Rev protein and with herpesvirus saimiri ORF57 protein [5][6][7]. However, for most viruses, consequences of viral protein localization in the nucleolus remain largely unknown [3,4].…”
Section: Resultsmentioning
confidence: 99%
“…The accumulation of Rip1p at two distinct NPC sites may reflect rate-limiting steps during that process. The vertebrate NPC-associated FGnucleoporins Nup98 and Nup153 recently have been proposed to move between the nuclear and cytoplasmic compartments in association with exported cargoes (Nakielny et al, 1999;Zolotukhin and Felber, 1999) An association of Rip1p with RNP cargo was suggested by the identification of an interaction between the human RNA export factor TAP and the FG-nucleoporins CAN/ Nup214 and hCG1, the functional homologues of Nup159p and Rip1p, respectively (Katahira et al, 1999;E.Izaurralde, personal communication;and Figure 2). These data support the view that TAP and its yeast homologue Mex67p promote the export of bound RNPs through an interaction with one or more FG-nucleoporins (de Castillia and Rout, 1999).…”
Section: Discussionmentioning
confidence: 98%